2021
DOI: 10.1101/2021.03.10.434822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Cell-Free DNA Methylation Patterns Unique to the Human Left Ventricle as a Potential Indicator of Acute Cellular Rejection

Abstract: Increased levels of donor-derived cell-free DNA (dd-cfDNA) in recipient plasma have been associated with rejection after transplantation. DNA sequence differences have been used to distinguish between donor and recipient but epigenetic differences could also potentially identify dd-cfDNA. This pilot study aimed to identify ventricle-specific differentially methylated regions of DNA (DMRs) that could be detected in cfDNA. We identified 24 ventricle-specific DMRs and chose two for further study, one on chromosom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Different tissues and cell types have been shown to have unique methylation patterns, which can also change in health, disease, and developmental stage (Figure 2), referred to as differentially methylated regions (DMRs) 66–68 . DMRs are an emerging mechanism used to identify the tissue of origin in a DNA sample 67–70 . This methodology has been applied in areas such as non‐invasive prenatal testing, cancer detection/treatment, solid organ transplantation, and detection of disease or damage in other situations such as type I diabetes, aortopathy, and traumatic brain injury based on DMRs identified in cfDNA 67–69 .…”
Section: Wbc Chimerismmentioning
confidence: 99%
See 1 more Smart Citation
“…Different tissues and cell types have been shown to have unique methylation patterns, which can also change in health, disease, and developmental stage (Figure 2), referred to as differentially methylated regions (DMRs) 66–68 . DMRs are an emerging mechanism used to identify the tissue of origin in a DNA sample 67–70 . This methodology has been applied in areas such as non‐invasive prenatal testing, cancer detection/treatment, solid organ transplantation, and detection of disease or damage in other situations such as type I diabetes, aortopathy, and traumatic brain injury based on DMRs identified in cfDNA 67–69 .…”
Section: Wbc Chimerismmentioning
confidence: 99%
“…[66][67][68] DMRs are an emerging mechanism used to identify the tissue of origin in a DNA sample. [67][68][69][70] This methodology has been applied in areas such as non-invasive prenatal testing, cancer detection/treatment, solid organ transplantation, and detection of disease or damage in other situations such as type I diabetes, aortopathy, and traumatic brain injury based on DMRs identified in cfDNA. [67][68][69] A key advantage of this method over those previously described is the potential to specifically identify DNA sequences as being derived from RBC precursors, reducing possible confounding by other sources of DNA.…”
Section: Nrbc Dna Methylationmentioning
confidence: 99%
“…A pilot heart study examined left ventricle DNA methylated patterns in cfDNA isolated from serial plasma samples (n = 24) taken at the time of surveillance biopsies and found increased levels of ventricle-specific cfDNA in the plasma of recipients diagnosed with 2R grade TCMR, but no correlation with less severe 1R grade rejection. 55 Gai et al provided a genetic-epigenetic tissue mapping strategy using tissue-specific DNA methylation patterns to determine the tissue composition of dd-cfDNA in 11 lung transplant recipients. 56 Interrogation of dd-cfDNA 72 h posttransplant found that 17% originated from lung tissue cells, whereas 78% derived from donor neutrophils and lymphocytes passively transferred within the allograft.…”
Section: Introductionmentioning
confidence: 99%